Analysis of Production Function in Layer Chicken Business in Soppeng District - Hasraful Anang; Syahriadi Kadir (Journal of Global Innovations in Agricultural Sciences)
Production function is one method to understand the effect of production inputs used in an effort to achieve maximum profit. This study aims to identify how the use of inputs has an influence on the production of layer eggs in Soppeng Regency. The research was conducted from August to October 2023 in Soppeng Regency. The number of samples was 67 layer breeders located in each sub-district in Soppeng Regency using Nonprobability sampling technique. Data were collected through observations and interviews. Data were analyzed using multiple linear regression with the Cobb-Douglass production function model, and tested through simultaneous tests and partial tests. Independent variables consisted of seedlings, labor, cage area, farmer experience, Newcastle Disease (ND) vaccine, Avian Influenza (AI) vaccine, concentrate feed, ground corn feed and bran feed. The dependent variable included production (eggs). The study showed tshat the use of inputs of seedlings, labor, cage area, farmer experience, Newcastle Disease (ND) vaccine, concentrate feed, and ground corn feed had a significant effect on egg production of laying hens in Soppeng Regency, while the variable Avian Influenza (AI) vaccine and, bran feed did not have a significant effect on egg production of laying hens in Soppeng Regency. So the practical implication of this research is that layer breeders in Soppeng Regency can increase egg production by focusing on the use of quality seeds, efficient labor, optimal utilization of cage area, increasing the experience and knowledge of farmers, as well as, the use of Newcastle Disease (ND) vaccine, concentrate feed and ground corn feed, while the use of Avian Influenza (AI) vaccine and bran feed should be re-evaluated because it does not have a significant impact on production. Keywords: Cobb-Douglass, Production Function, Production Inputs, Egg Production, Laying Hens.